2020
DOI: 10.1186/s12876-020-01275-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative platelet-to-lymphocyte ratio predicts poor prognosis of patients with primary gastrointestinal stromal tumor

Abstract: Background: The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are considered to reflect the systemic inflammatory response and clinical prognosis. However, the independent prognostic values of the NLR and PLR for patients with gastrointestinal stromal tumor (GIST) remain debatable. This study aims to evaluate the prognostic value of preoperative NLR and PLR in GIST patients. Methods: We retrospectively reviewed all GIST patients diagnosed and surgically treated at Union Hospital b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Several studies have been performed to evaluate the impact of COVID-19 on the gut microbiome. The first study on 15 patients demonstrated a gut microbiome fingerprint characterized by a decrease of the beneficial commensals and increase of opportunistic pathogen [ 245 ]. This dysbiosis was associated with the severity of the disease.…”
Section: Covid 19: Relevance Of Host Genetic Factorsmentioning
confidence: 99%
“…Several studies have been performed to evaluate the impact of COVID-19 on the gut microbiome. The first study on 15 patients demonstrated a gut microbiome fingerprint characterized by a decrease of the beneficial commensals and increase of opportunistic pathogen [ 245 ]. This dysbiosis was associated with the severity of the disease.…”
Section: Covid 19: Relevance Of Host Genetic Factorsmentioning
confidence: 99%
“…In addition, a series of studies have reported that many inflammation-based markers were directly related to poor prognosis or post-operative complications in patients with hip fracture, including prognostic nutritional index ratio (PNI) [ 9 ], CRP/PNI ratio [ 10 ], and neutrophil-to-lymphocyte ratio (NLR) [ 11 , 12 ]. Platelet-to-lymphocyte ratio (PLR), a novel marker of systemic inflammation, has been reported to be closely related to the prognosis of many diseases, such as inflammatory diseases [ 13 ], cardiovascular disease [ 14 ], and various malignancies [ 15 17 ], even in the 2019-novel coronavirus disease (COVID-19) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence has demonstrated that high neutrophil‐to‐lymphocyte ratio (NLR) or platelet‐to‐lymphocyte ratio (PLR) levels were associated with worse prognosis in patients with surgically resected GISTs. However, the role of these markers still lacks sufficient evidence and remains controversial 9,10 . This suggests us that nutritional status could be a potential prognostic predictor for GIST patients.…”
Section: Introductionmentioning
confidence: 99%